ADDITION OF COCONUT SUGAR AND TIME OF FERMENTATION ON QUALITY OF RED BEANS MILK FERMENTED (Phaseolus vulgaris L. - Noviar Harun; Rahmayuni '; Yucha Eklesia Sitepu (Jurnal Sagu, 2013)
The aim of the research was to determine the effect of coconut sugar, time length of fermentations and theirinteraction on the qualities of the red beans (Phaseolus vulgaris L.) fermented milk. The design of theexperiment was faktorial 3x3 and arranged by the Randomized Complete Design (RCD) with threereplications. The first faktor was coconut sugar content (3, 6 and 9)%. The second factor was times of thefermentation (16, 18 and 20) hours. The result showed the adding of coconut sugar content and time lengthof fermentations affected on pH and total titrated acid. The interaction between coconut sugar content andtime length of fermentations was not affected to pH, total titrated acid, total lactid acid bacteria and proteincontent. It was concluded that the best quality of red beans (Phaseolus vulgaris L.) fermented milk was onthe 9% of coconut sugar content and 16 hours fermentation (G3T1).Key words: coconut sugar concentration, fermentation duration, red beans and milk fermented.